Kombinasi Metode ROC-SAW Untuk Analisis Efisiensi Bahan Bakar Kendaraan LSUV - Santoso Setiawan; Suryanto (LPPM Universitas Bina Sarana Informatika, 2025)
The SAW (Simple Additive Weighting) method, also known as the Scoring Method or Weighted Sum Method, is a simple yet effective multi-criteria decision-making technique. SAW works by calculating the total sum of weighted scores for each alternative. However, this method is sensitive to weights, so subjective weight selection can affect the final results. The purpose of this study is to determine the effectiveness of combining two decision support methods to be implemented in comparing fuel-efficient LSUV (Low Sport Utility Vehicle) vehicles. The methods used are ROC (Rank Order Centroid) for weighting criteria and SAW (Simple Additive Weighting) applied to multi-criteria decisions in determining the performance ranking of each vehicle. After in-depth analysis, this study shows that the combination of the ROC and SAW methods can provide a clear picture of the advantages of each vehicle and is effective for assessing the fuel efficiency of LSUVs in Indonesia based on the established criteria. The conclusion of this study provides recommendations on the use of a combination of these two methods for more accurate and effective analysis in supporting decision making.